Spindle Cell Lipomas of the Respiratory Tract: A Case Report and Comprehensive Literature Review. (November 2019) - Reid, Jonathan; Wehrli, Bret; Sowerby, Leigh J.
Background: Spindle cell lipomas (SCLs) are benign tumors that are characteristically present on the upper back and neck, but in rare cases present throughout the respiratory mucosa, causing hoarseness, stridor, dyspnea, and obstruction. Objective: To highlight the importance of considering SCL in the diagnosis of benign respiratory tract tumors, a literature review identified all published cases of respiratory tract SCLs, including 2 from our institution: one case in the nasopharynx and 1 in the nasal valve. Methods: All case reports, series and literature reviews from the English literature from 1975 through March 2018 were systematically identified for review in the MEDLINE, EMBASE, and Scopus databases. Two additional cases from our institution were described. Results: In total, 24 cases of SCL in the respiratory tract were identified for review. Two cases from our institution are described here, bringing the total of reported cases to 26. Extensive analyses of oral cavity SCLs already exist, so we excluded this site from our review and focused on sites where SCLs may present with respiratory symptoms. Excluding the oral cavity and oropharynx, the most common location described is the larynx. All 26 cases were treated with excision. One tumor required a second surgery, but there were no other complications nor recurrences. Conclusion: Although rare, SCLs may arise from throughout the respiratory tract and cause dyspnea, hoarseness and stridor. Spindle cell lipoma should be considered in the differential diagnosis of a respiratory tract mass. This diagnosis confers a good prognosis and patients may be reassured that surgery is almost always curative.